ANALYSIS OF THE ANALYTIC HIERARCHY PROCESS (AHP) METHOD IN DETERMINING PRIORITY DECISIONS FOR HANDLING STUNTING IN BENGKULU PROVINCE - Rewan Jayadi; Ramya Rachmawati; Siska Yosmar (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2024)
Statistical Processing Data 2021 shows that technical efficiency in stunting intervention costs in Bengkulu Province always achieves efficient results in the technical system, however, for that reason, it is technically inefficient in costs. This research aims to analyze the Analytical Hierarchy Process (AHP) method in deciding to determine priorities for handling stunting in Bengkulu Province, which will then get results according to the level of needs of each district/city. This study used the AHP method to determine priorities for handling stunting by collecting primary data directly from respondents, namely the Bengkulu Province Health Service. Validity and reliability tests are used before researching to obtain good research results suitable for development. The results of the consistency test showed that the Consistency Ratio (CR) value for each criterion and the alternative was, which means that the filling and results of the questionnaire for respondents had obtained results that met the requirements. The results of the analysis of preferences for criteria/alternatives show that the main priority in making decisions for handling stunting in Bengkulu Province is North Bengkulu as the main priority, followed by South Bengkulu, Seluma, Rejang Lebong, Kepahiang, Central Bengkulu, Bengkulu, Mukomuko, Lebong, and finally Kaur. Keywords: Analytic Hierarchy Process, Consistency Ratio, stunting, Bengkulu Province.